CO oxidation by MoS2-supported Au19 nanoparticles: effects of vacancy formation and tensile strain. Issue 19 (27th April 2016) - Kwon, Soonho; Shin, Kihyun; Bang, Kihoon; Kim, Hyun You; Lee, Hyuck Mo
Abstract : The mechanism of the catalytic oxidation of CO activated by MoS2 -supported Au19 nanoparticles (NPs) was studied using density functional theory calculations. Abstract : The mechanism of the catalytic oxidation of CO activated by MoS2 -supported Au19 nanoparticles (NPs) was studied using density functional theory calculations. Of particular interest were the effects of the physical/chemical modification of a MoS2 support on the CO oxidation pathway and the activation of specific reactive centers, i.e., the Au atoms of Au19 or the Au–MoS2 perimeter sites. We systematically modified MoS2 by introducing an S vacancy or 5% tensile strain and studied the shift of each reaction step and the overall change in the reaction pathway and activity. Despite the lack of direct involvement of the Au–MoS2 perimeter in the reaction, the combination of an S vacancy and the tensile strain in the MoS2 support was found to improve the stability and catalytic activity of Au NPs for CO oxidation. The results show that support modification can provide information for new pathways for the rational design of Au-based catalysts.